Effect of H2S and NH3 in biomass gasification producer gas on CO2 capture performance of an innovative CaO and Fe2O3 based sorbent - Dashtestani, F.; Nusheh, M.; Siriwongrungson, V.; Hongrapipat, J.; Materic, V.; Pang, S. (My University, 2021)
This study has investigated the effect of contaminants in biomass gasification producer gas on the CO2 capture performance of an innovative CaO and Fe2O3 based sorbent material. It is well known that biomass gasification producer gas contains gaseous contaminants such as H2S and NH3. Experiments were conducted with the combined contaminants of H2S at 230 ppmv and NH3 at 2300 ppmv. Each run of the experiment included three major stages: H2 reduction, CO2 capture (carbonation) and CO2 release (calcination). The operation temperature was controlled at 650 °C with a duration of 3 h at the carbonation stage, and at 850 °C with a duration of 2 h at the calcination stage. In each experiment, three cycles of carbonation-calcination were performed. The experimental results show an average CO2 capture efficiency of 61.8% during the carbonation stage in the first cycle, reducing to 45.4% in the third cycle. However, effective CO2 capture was achieved in the initial 20 min of carbonation, with a capture efficiency of 75.1% for the first cycle and 62.8% in the third cycle. It was found that the CO2 sorbent can effectively remove contaminants from the producer gas, showing catalytic effect of the sorbent material. The H2S removal efficiency decreased from 99% in the first cycle to 82% after three cycles, while the NH3 removal efficiency was above 99% for all three cycles during the carbonation stage. Furthermore, concentrations of the N-based and S-based compounds in the outlet gas streams during calcination were examined for the potential impact when the gas is injected into plant nursery greenhouses for growth enhancement. Fundamental analysis was also performed and microstructural changes in the material were examined to understand the CO2 capture process by the tested sorbent.
Keywords: Biomass gasification; CaO-Fe2O3 sorbent; Carbonation-calcination looping; CO2 capture; H2S adsorption; NH3 decomposition